Advanced AI and big data techniques in E-finance: a comprehensive survey - Rihab Najem; Ayoub Bahnasse; Meryem Fakhouri Amr; Mohamed Talea (Discover Artificial Intelligence)
Abstract The finance sector is one of those that have had a dramatic change after the integration of technology and more so Artificial Intelligence, Big Data, Text Mining and Cloud computing which has also given way to the development of e-finance where electronic channels together with digital technologies are used to deliver financial services. E-finance takes advantage of these new technologies to provide easy, efficient, and innovative financial services to people. This makes it possible for DFI to reduce expenses, make data-informed decisions and improve their experience for clients but also opens access to financial services for people in emerging markets. Advances need to ensure data protection and secrecy for the well and confidence in financial industry as well: research will scrutinize effects due technological progress on AI plus Big Data, Text Mining or Cloud Computing within Finance. This paper attempts a comprehensive review of literature through scholarly articles and papers published over the past thirteen years (2013–2025) available through Google Scholar and SCOPUS. The research methodology proceeded by choosing and crossing keywords related to technology and fintech, based on a bibliometric analysis of the past and current literature of related fields, the frequency of citation, and usage in emerging AI, Big Data, Text Mining, and Cloud computing trends in finance. Wide coverage was pursued by considering expert-reviewed high-ranking keywords drawn from the core areas of the field. The results identify the top publishers and journals holding significant influence in the field of E-finance. Moreover, this paper will also shed light on the possible benefits of text mining in finance which include improving customer satisfaction as well as detecting and preventing fraudulent transactions and risks mitigation. Results underscore the co-dependence between Finance, Technology, AI, Big Data, Text Mining, Cloud. And how they fit with each other; it further proposed a new methodology that detailed using multi-source datasets. However, these findings form valuable insights into the growing importance of emerging technologies upon the finance industry and current key trends in this area.